Dismissed Mines: From the Past to the Future - Varriale, Roberta; Aldighieri, Barbara; Genovese, Laura (Heritage, 2023)
Today, dismissed mines are considered significant local tangible and intangible cultural heritage elements and they are more and more often at the core of dedicated enhancement processes, being sometimes inscribed in the UNESCO list; included in geoparks; transformed worldwide into industrial museums; or reused. Italy has a peculiar approach to the topic even if it has been underestimated, and research in the field might be improved. Which models should be looked at? Is it possible to identify some basic criteria to look at to obtain positive results? If yes, where should one start? Our proposal is that the application to the newly born class underground built heritage (UBH) can provide instruments for their historical functional classification and introducing several criteria for their interpretation and reuse could eventually support future enhancement projects in this specific sector. This methodology has been already applied worldwide to this category of good, giving positive results and motivating the authors to continue the research following this hypothesis, with the aim of creating a framework of good practices to be used as a reference for new projects. This paper summarizes the authors’ research in this direction. After the introduction of the academic scenario and the UBH theoretical approach, this study proposes the results from applying this new methodology to several worldwide case studies from Greece, Germany, Italy, Japan, and Poland in order to evaluate best practices and/or unsuccessful stories. This study, based on data collected during onsite inspections by the authors within several international financed projects, consists of two steps. In the first, a general overview of all the aspects connected to the historical and contemporary reuses of dismissed mines under analysis was carried out, proposing a reclassification on the basis of the UBH methodology. The second section is dedicated to a new case study: Valle Imperina dismissed mines complex. This section includes an analysis of tangible and intangible values connected to the site and that of the state of the art of the corresponding enhancement. At the end, an evaluation of its potentialities and some critical issues was conducted.